Benzodiazepínicos : um estudo da indicação/prescrição no município de Coronel Fabriciano-MG, 2006 - Karleyla Fassarella Firmino (2008)
The Benzodiazepines (BZD) are the most commonly used group of sedative medicines and their use must be guided by the administration of the smallest therapeutical doses to the shortest period of time possible due to the risks of dependence and abuse. Their inadequate use is widely described in literature and has individual and collective implications and for that reason has become object of relevance to the public health. This study evaluated the adequacy of the prescriptionsof BZD for users of the local public health service of Coronel Fabriciano-MG and the profile of the patient who received the prescription. All prescriptions of BZD provided at the Basic Health Units (UBS) of Coronel Fabriciano from September/2006 to October 2006, as well as the forms of clinical indication and the computerized register of the local pharmacy system were used as data source in this study. 1,866prescriptions were analyzed, 59.7% of them referred to Diazepan 10 mg and the rest to Clonazepan 2 mg. Women constituted 74.3% of the sample. The average age of the patients was 49,75, with about 25% of precription for elderly patients. The period of continuous treatment with BZD was superior to one year for more than 50% of the samples. The BZD use had greater prevalence among patients who participate of thecollective programs of hipertension and diabetes and who are not inserted in the work market. The main indications were as hypnotic (33.8%) and anxiolytic (24.2%), however 21.9% was for chronic/dependendable use according to what was informed by the prescribers. It was observed that about 60% of the BZD prescriptionswere inadequate, considering its indication and the time of treatment. The average age was superior among patients who used BZD inadequatelly. It was also observed the predominancy of the consumption of Diazepan among those patients who made an inadequate use of BZD. It was found an association between the prescription of BZD and other psychotropics, particularly among individuals with insertion in the work market. The standard of BZD use in Coronel Fabriciano is similar to the one inliterature and demonstrates the importance of studying the use of BZD in the detection of problems with prescription. The study indicates the necessity for the adoption of educative and normative measures which can rationalize the use of these medicines minimizing their abusive and inadequate use.